Culturally Tailored Community Brain Health Education for Chinese Americans Aged 50 or Above: A Mixed-Methods Open Pilot Study - Kaipeng Wang; Fei Sun; Peiyuan Zhang; Carson M. De Fries; Xiaoyouxiang Li; Jie Zhu; My Ngoc To (Geriatrics)
Background: Chinese Americans, the largest Asian American subgroup in the U.S., face linguistic, cultural, and socio-economic barriers to dementia prevention. To promote brain health in this population, a culturally tailored community approach is essential. This study evaluates a culturally tailored community brain health education program to enhance brain health knowledge and motivate lifestyle changes to prevent the risk of dementia among Chinese Americans aged 50 or older. Methods: The program was developed and evaluated in four phases. First, we assessed participants’ interests in brain health topics, availability, and preferred delivery modes. Next, experts on the identified topics developed educational content and outcome assessments. The third phase focused on implementing a six-session program covering general knowledge about Alzheimer’s disease and related dementias, diet, sleep, physical exercise, health checks, and mindfulness. Finally, we evaluated the program’s feasibility and effectiveness using pre–post surveys, feedback questionnaires, and focus groups. Results: Seventy-seven participants registered for the program, and sixty-nine (90%) attended at least four sessions. The quantitative results, based on paired t-tests, showed significant increases in brain health knowledge, sleep quality, and behavioral motivation for lifestyle changes, and a decrease in depressive symptoms, with two-tailed p-values lower than 0.05. The qualitative results further revealed promising feasibility and acceptability, as well as the perceived benefits of the program. Conclusions: The findings highlight the feasibility, acceptability, and potential effectiveness of a culturally tailored community education approach for promoting brain health and lifestyle changes. Sustained community outreach and education efforts among Chinese Americans are needed.